Islamic Education In West Sumatra: Historical Point Of View - Baharuddin, Rahmawati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2004)
This paper focuses on a brief history of growth and development Islamic education in Minangkabau before and after the emergence of the movement Muhammadiyah renewal. The development of Islamic education itself began to coincide with the arrival of Islam in West Sumatra. The idea of a reformist movement Muhammadiyah in the social-religious field in the 20th century gave a major contribution to the development of Islamic modernism in West Sumatra and has given color to the education system in Indonesia.